The Factors That Cause of Delays in Medicolegal Reporting Process - Turla, Ahmet; Uygul, Elif Sazak; Zekioğulları, Meltem; Aydın, Berna (The Bulletin of Legal Medicine, 2018)
Objective: In this study, it is aimed to analyze what effect we have on the prolonged judicial proceeding in the field of forensic medicine and to discuss the results. Materials and Methods: In this study; legal/medical files of 232 cases which were sent to Ondokuz Mayıs University Faculty of Medicine, Forensic Medicine Department for medicolegal report preparation in 2017 were examined retrospectively. All the steps in the period between the date of the demand letter to request medicolegal report and the date of prepared report was sent from the hospital were examined separately. The obtained data were analyzed with SPSS software package (Version 15.0). Results: The mean time between the date of application to our department and the date of the report was prepared is 11,4±26,9 days, the mean time between the date of the report was prepared with the date of report was signed and sent to judicial authorities is 3,8±2,8 days. The mean time of requested consultations from other departments for 73 cases is 5,8±17,9 days. The mean time between requesting and resulting of radiological or medical workup for 12 cases who were scheduled for workup is 18,2±20,8 days. Conclusion: No matter how small the effect of reporting process in prolonged judicial proceedings, we think it is important shortening this period which is in our responsibility for reducing the victimization of people.